2020
DOI: 10.1021/acsabm.0c00637
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effect of Nanolignin and Metal Oxide Nanoparticles into Poly(l-lactide) Bionanocomposites: Material Properties, Antioxidant Activity, and Antibacterial Performance

Abstract: Binary and ternary poly(L-lactide) (PLLA)-based nanocomposites, containing nanolignin (1 wt %) and different metal oxide nanoparticles (0.5 wt %, Ag 2 O, TiO 2 , WO 3 , Fe 2 O 3 , and ZnFe 2 O 4 ), were realized by solvent casting, and their morphological, thermal, surface, optical, antioxidant, and antimicrobial characterizations were performed. The presence of metal oxide nanoparticles at the selected weight concentration affects the surface microstructure of the PLLA polymer, and this outcome is particle-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Results of FESEM analysis of LNP ( Figure 1 a) showed that the nanoparticles have diameters in the range of 50 ± 20 nm [ 35 , 40 ] and appear in the form of aggregates: this phenomenon is related to the hydrodynamic radius of colloidal lignin in aqueous suspension, that can be influenced by different parameters, such as temperature, pH [ 41 , 42 ], and lignin concentration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results of FESEM analysis of LNP ( Figure 1 a) showed that the nanoparticles have diameters in the range of 50 ± 20 nm [ 35 , 40 ] and appear in the form of aggregates: this phenomenon is related to the hydrodynamic radius of colloidal lignin in aqueous suspension, that can be influenced by different parameters, such as temperature, pH [ 41 , 42 ], and lignin concentration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another possible route explored for the development of high-value usage lignin-based materials is hybridization with the inorganic components. 12 , 13 , 26 Lignin can be associated with the inorganic nanomaterials that form lignin-based hybrid nanocomposites. Hybridization changes the chemical nature and reactivity of lignin.…”
Section: Lignin Structural Featuresmentioning
confidence: 99%
“…Because of the neutral 3D network, lignin can afford the uniform lignin/inorganic nanocomposite system when it combines with the inorganic nanoparticles/metals. 26 The resultant lignin-based nanomaterials can be used as high-value-added materials for potential applications in various biomedical domains, particularly in drug/gene delivery and tissue engineering due to synergetic interactions from both organic lignin and inorganic nanocomposites. 12 , 13 , 26 The binding ability of lignin with nanomaterials or other multivalent metal ions involves active functional groups (phenol, hydroxyl, and carboxyl groups), which act as both chelating and reducing agents to the metal center.…”
Section: Lignin Structural Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts are aimed at reducing the dependency on fossil carbon feedstocks and to fully utilize the plant-based resources, for example, in products relevant to the resin and plastic industries. Many applications such as bio-medical and nutritional materials under development strive to take advantage of lignins' antioxidant activity, [10][11][12][13] or its high carbon content attractive to carbonaceous materials in the form of fibers and electroactive components. 14 Owing to its amphiphilic structure, lignins have been shown to be surface-active and are able to improve the strength at interfaces, for example, in adhesives.…”
Section: Introductionmentioning
confidence: 99%